Respuesta :

Answer:


Step-by-step explanation:


Ver imagen iamjinburger

Answer:

Answer: 5

Step-by-step explanation:

Remark

Start with the meaning of g[f(x)]. This when you write g(x), where ever you see and x in g(x), put in an f(x)

g(f(x))

g(x)= x + 1                     Substitute f(x) for x

g(f(x)) = f(x) + 1              Substitute x^2 for f(x)  

g(f(x)) = x^2 + 1              

g(f(-2)) = (-2)^2 + 1        Substitute -2 for x

g(f(-2)) = (4) + 1              

g(f(-2)) = 5                    Answer